Comparison for colloidal stability and aggregation behavior of fulvic and humic acids: effects of cations and pH - Wang, Chun li; Xu, Chen-yang; Ma, Ren-tian; Li, Qi-rui; Hu, Fei-nan; Zhao, Shi-wei; Bol, Roland (Frontiers in Soil Science, 2025)
Fulvic acid (FA) and humic acid (HA) are organic materials that can form complexes with metal ions, playing a crucial role in predicting the behavior of organic colloids. The colloidal stability values of FA and HA vary with pH and specific cations, but this has rarely been comprehensively examined. This study systematically compared the aggregation kinetics and colloidal stability of FA and HA and the mechanisms behind their behavior based on particle interaction theory. The results showed that higher pH values stabilized FA and HA colloids by increased electrostatic repulsive energy. Additionally, increased electrolyte concentration destabilized FA and HA colloids by cationic polarization (chemical bond formation). The cation aggregation ability followed the order Ca2+ > Mg2+ > K+ > Na+, showing that the specific ion effects induced by non-classical polarization resulted from the strong electric field of the highly negatively charged FA and HA. With pH values ranging from 5 to 7 and 9, FA and HA were stabilized through raising the critical coagulation concentrations (CCCs) in NaCl and KCl. With increasing pH, the enhanced electrostatic repulsive energies in the Na+ and K+ systems resulted in weaker aggregation behaviors due to the deprotonation of the hydroxyl and carboxyl groups of colloids. Compared with HA, FA had a lower Hamaker constant, higher surface negative charges, larger CCCs, and stronger dispersion stability. This work will contribute to the understanding of organic colloidal aggregation mechanisms and act as a reference to predict their environmental behaviors.